Adaptions to the National Diabetes Prevention Programme lifestyle change curriculum by Hawai‘i Federally Qualified Health Centers: a qualitative descriptive study - Tetine Sentell; Catherine Pirkle; David Stupplebeen; Jermy-Leigh Domingo; Blythe Nett; L Brooke Keliikoa (BMJ Open)
Objective The objective of this qualitative study was to describe the community-appropriate and culturally appropriate adaptations made by lifestyle change programme (LCP) coaches to the National Diabetes Prevention Programme curriculum for Federally Qualified Health Center (FQHC) patients in Hawaiʻi, an ethnically diverse state with a high proportion of Native Hawaiians and Pacific Islanders (NHPI).Research design and methods We used a qualitative descriptive approach. First, we conducted a document review of existing programmatic notes and materials followed by video interview calls with 13 lifestyle coaches at 7 FQHCs implementing in-person LCPs. Lifestyle coaches catalogued, described and explained the rationale for adaptations. The research team counted adaptations if they met a specific adaptation definition derived from several sources. Community and cultural relevancy of adaptations were analysed using an existing framework for weight loss and diabetes prevention for NHPIs.Results The average number of adaptations per FQHC was 8.61 (range: 4–16). Adaptations fell into 11 broad categories such as off-site community field trips, food-related and nutrition-related activities, and physical activity opportunities. Novel adaptations included goal setting with motivational interviewing and dyadic recruitment. Field trips and in-class food demonstrations addressed the most constructs related to weight loss and diabetes prevention for NHPI, including social and community barriers, familial barriers and barriers to self-efficacy.Conclusions Lifestyle coaches were culturally attuned to the needs of LCP participants, particularly from NHPI communities. Policy-makers should recognise the extra work that LCP coaches do in order to increase enrollment and retention in these types of programmes.